THE PRESENTATION OF SELF IN THE ONLINE SOCIAL NETWORK - A. A. Shirmazanyan (Vestnik MGIMO-Universiteta)
The author analyzes online social network as a social institute of a virtual type where individuals can present themselves to others by means of special practices. At the same time he indicates that these practices are similar to real ones by their relative equality in particular space and time due to reflexivity of actors. There are three major functional regulators of users behavior in online social network: 1) quantitative restrictions on self presentation determined by information formats; 2) qualitative matter of self presentation conditioned on norms of Russian and International legislations; 3) rituals of virtual interaction. The study shows what role VK-user profile plays in modern human interactions and how it affects communication practices. Case-study analysis of the standard form of VK-user profile allowed to learn the features of communication tools of the social network that on the whole are used for exchanging self-presentation data between its users. The author particularly focuses on instrumental capabilities of a section of VK-user profile form called “Personal views” that includes closed questions about existential and social values. A person can partially present him/her self in the network by selecting a short templated response to each closed question from a narrow range of alternatives. The study also considers the functions of authorized pages of celebrities who are some kind of “significant others” to their multiple admirers.